Steroid receptor coupling becomes nuclear - Galigniana, Mario Daniel (2012)
In this issue of Chemistry & Biology, Grossman et al. report a study on aldosterone-dependent nuclear translocation of the mineralocorticoid receptor (MR). They analyze the dependency of MR retrotransport, DNA-binding, and transcriptional activity on Hsp90 and demonstrate that MR dimerization is a nuclear event.